A novel Sm3+ singly doped LiCa3ZnV3O12 phosphor: a potential luminescent material for multifunctional applications. Issue 58 (27th September 2018) - Guo, Heng; Devakumar, Balaji; Vijayakumar, R.; Du, Peng; Huang, Xiaoyong
Abstract : Sm 3+ ion singly doped LiCa3 ZnV3 O12 phosphors were developed for multifunctional applications in indoor illumination, optical thermometry, and safety signs. Abstract : The Sm 3+ ion singly doped LiCa3 ZnV3 O12 (LCZV) phosphors were synthesized by a traditional high-temperature solid-state method. The luminescence characteristics of the as-prepared samples were studied by photoluminescence excitation and emission spectra. Under 343 nm excitation, the synthesized phosphors exhibited color controllable emission induced by the efficient energy transfer from VO4 3− groups to Sm 3+ ions. Besides, the energy transfer efficiency was revealed to be about 58.4% when the dopant concentration was 4 mol%. By utilizing the as-prepared LCZV:Sm 3+ phosphors, commercial BaMgAl10 O7 :Eu 2+ blue-emitting phosphors and a near-ultraviolet light-emitting diode (LED) chip, a white LED device was fabricated. Under an injection current of 100 mA, the packaged LED device emitted pure white light with high color rendering index (88.4) and proper correlated color temperature (4320 K). By analyzing the thermal quenching behavior of the VO4 3− groups and Sm 3+ ions, the optical thermometric behavior of the Sm 3+ -doped LCZV compounds was investigated. The maximum absolute sensor sensitivity and relative sensor sensitivity were found to be 0.25 K −1 and 1.8% K −1, respectively. Additionally, the emitting color of the studied samples was dependent on the temperature. Ultimately, the Sm 3+ -doped LCZV phosphors were potential candidates for indoor illumination, optical thermometry and safety signals in high temperature environments.